The translation of legal texts on the basis of Skopostheorie (in Greek) - Vlachopoulos, Stefanos (International Journal of Speech, Language and the Law, 2001)
The aim of the thesis is to examine the feasibility of translating legal texts for different purposes (skopoi), to establish linguistically the comparative degree of difficulty for the two combinations English–Greek and German–Greek and to propose a model for the teaching of specialized translation. The theoretical infrastructure for the first aspect is the Skopostheorie. This theory, introduced by the German scholars Reiss and Vermeer, propounds a functional approach to translating, where the translator detaches himself from the source text and prioritizes the skopos or purpose and the effect of the translation on the final recipient. Randomly selected professional translators rendered a particular German lease (civil law) and a particular English lease (common law) into Greek (civil law) for one specific skopos each. The translators did not know that the translations would be used for research purposes. The designated skopoi were selected on the basis of my experience as a translator. In the first skopos the translators were asked to render both the English and the German original for a layman with no legal knowledge; in the second skopos they had to translate for a comparative lawyer wishing to become acquainted with the formulation of leases in the legal source system, while in the third skopos the translated text was bound for a Greek court. The analyses of the way the lexicon, the syntax and the textlinguistic features of the source texts were translated for each skopos revealed that none of the source texts were translated adequately as a whole. However, indications were found within nearly every translation that a skopos-oriented rendering of legal texts is possible. For example the common law term landlord was rendered into Greek by the term ekmisqwt–z (lessor), which is the one used in Greek leases (functional equivalent), and not by the term idiokt–tjz (owner, landlord) thus depriving the comparative lawyer of the denotation of the source term. However, the translation of the term landlord as ekmisqwt–z was considered acceptable in the case of the layman recipient. Comparing the translation processes for both pairs, the higher degree of difficulty for the translation from English (common law) into Greek (civil law) could be proven experimentally, since for the transfer of meaning from one legal system into another the translator has to consider more linguistic and legal parameters than in the translation of the German lease (civil law) into Greek (civil law). Finally, a model for teaching specialized translation structured around Skopostheorie and the feasibility of translating legal texts for different skopoi was introduced. The manipulation of the skopos for a particular text allows the instructor to increase gradually the difficulty of the task by asking the students to translate in the early stages for skopoi which demand only a minimum of effort, for example to inform a potential client about the content of a text. Later the task would be to translate a text for someone interested in the structure of the source text, but who is ignorant of the language, while the third level would be to ask the student to produce a functionally equivalent text. That way the students gradually acquire the necessary skills for a skopos-oriented translation and become aware of the limits of language and the wider meaning of the term translation.